-2n-6(1-10n)=-4n-9(-6-8n)

Simple and best practice solution for -2n-6(1-10n)=-4n-9(-6-8n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2n-6(1-10n)=-4n-9(-6-8n) equation:


Simplifying
-2n + -6(1 + -10n) = -4n + -9(-6 + -8n)
-2n + (1 * -6 + -10n * -6) = -4n + -9(-6 + -8n)
-2n + (-6 + 60n) = -4n + -9(-6 + -8n)

Reorder the terms:
-6 + -2n + 60n = -4n + -9(-6 + -8n)

Combine like terms: -2n + 60n = 58n
-6 + 58n = -4n + -9(-6 + -8n)
-6 + 58n = -4n + (-6 * -9 + -8n * -9)
-6 + 58n = -4n + (54 + 72n)

Reorder the terms:
-6 + 58n = 54 + -4n + 72n

Combine like terms: -4n + 72n = 68n
-6 + 58n = 54 + 68n

Solving
-6 + 58n = 54 + 68n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-68n' to each side of the equation.
-6 + 58n + -68n = 54 + 68n + -68n

Combine like terms: 58n + -68n = -10n
-6 + -10n = 54 + 68n + -68n

Combine like terms: 68n + -68n = 0
-6 + -10n = 54 + 0
-6 + -10n = 54

Add '6' to each side of the equation.
-6 + 6 + -10n = 54 + 6

Combine like terms: -6 + 6 = 0
0 + -10n = 54 + 6
-10n = 54 + 6

Combine like terms: 54 + 6 = 60
-10n = 60

Divide each side by '-10'.
n = -6

Simplifying
n = -6

See similar equations:

| Ab+3c=2xform | | 0.20+(0.30)(25)=(0.27)(x+25) | | 4(2x-6)=5(x+4) | | 8x=158 | | 2(x+0.5)=24 | | -45x+270=y | | 5y-2(y+2)= | | 6/10=p/4 | | 15y-45x=-30 | | -45+270=y | | 2/4=5v/5 | | -w-7=w+41 | | 12n^2-18n=0 | | 3k-5k=7k+7 | | 8/3=2/r | | m-30=-m-4 | | t/4-8=9 | | 5x^2-32x+10=0 | | n/7=5/4 | | -k=x^2-6x | | -12=6+4t | | 7(2x-2)-6(3-3x)=0 | | -x+3=x+37 | | y=-7(17/18) | | 5-3(x-9)=5(x+4) | | 5h+h-4hy+1-2h= | | 9(1/3)-(3/4)(-5) | | log(8x+3)=1 | | a+93=-a+5 | | (-25)+v=(-47) | | a/3+6=16 | | X+230=400 |

Equations solver categories